Urethral Hairballs as a Long-Term Complication of Hypospadias Repair: Two Case Reports - Spyridon Kampantais; Charalampos Dimitriadis; Leonidas Laskaridis; Ioannis Perdikis; Petros Kirtsis; Chrysovalantis Toutziaris (Case Reports in Urology)
Many times hair-bearing urethral grafts have been used inadvertently in the treatment of hypospadias. This can be accompanied with numerous troublesome long-term complications such as formation of stones, diverticula, and hairballs. We report two cases of men with a history of hypospadias repair being affected by such complications. We also discuss about their management and the effect of thioglycolic acid instillation to stop hair growth in the urethra mucosa in the second case.